The Interaction between Arbuscular Mycorrhizal Fungi and Endophytic Bacteria Enhances Plant Growth of Acacia gerrardii under Salt Stress - Hashem, Abeer; Abd_Allah, Elsayed F.; Alqarawi, Abdulaziz A.; Al-Huqail, Asma A.; Wirth, Stephan; Egamberdieva, Dilfuza (Frontiers in Microbiology, 2016)
Microbes living symbiotically in plant tissues mutually cooperate with each other by providing nutrients for proliferation of the partner organism and have a beneficial effect on plant growth. However, few studies thus far have examined the interactive effect of endophytic bacteria and arbuscular mycorrhizal fungi (AMF) in hostile conditions and their potential to improve plant stress tolerance. In this study, we investigated how the synergistic interactions of endophytic bacteria and AMF affect plant growth, nodulation, nutrient acquisition and stress tolerance of Acacia gerrardii under salt stress. Plant growth varied between the treatments with both single inoculants and was higher in plants inoculated with the endophytic B. subtilis strain than with AMF. Co-inoculated A. gerrardii had a significantly greater shoot and root dry weight, nodule number, and leghemoglobin content than those inoculated with AMF or B. subtilis alone under salt stress. The endophytic B. subtilis could alleviate the adverse effect of salt on AMF colonization. The differences in nitrate and nitrite reductase and nitrogenase activities between uninoculated plants and those inoculated with AMF and B. subtilis together under stress were significant. Both inoculation treatments, either B. subtilis alone or combined with AMF, enhanced the N, P, K, Mg and Ca contents and phosphatase activities in salt-stressed A. gerrardii tissues and reduced Na and Cl concentration, thereby protecting salt-stressed plants from ionic and osmotic stress-induced changes. In conclusion, our results indicate that endophytic bacteria and AMF contribute to a tripartite mutualistic symbiosis in A. gerrardii and are coordinately involved in the plant adaptation to salt stress tolerance. Key words: AMF, endophyte, Acacia gerrardii, salinity, nutrition